No evidence of expectancy effect on visuospatial attention in cognitive training with action video games - Gonçalves, Edimilson dos Santos (2024)
Dissertação (mestrado) — Universidade de Brasília, Instituto de Psicologia, Departamento de Processos Psicológicos Básicos, Programa de Pós-Graduação em Ciências do Comportamento, 2024.